Stereo-complementary bioreduction of saturated N-heterocyclic ketones. (May 2017) - Li, Chao; Liu, Yan; Pei, Xiao-Qiong; Wu, Zhong-Liu
Highlights: Ketoreductases READH and Ch KRED20 were applied in asymmetric bioreduction. Saturated N -heterocyclic ketones with a five- to seven-membered ring were reduced. Stereo-complementary reduction was achieved with excellent selectivity. Isopropanol was used as both the ultimate reducing agent and co-solvent. Abstract: The asymmetric bioreduction of several saturated N -heterocyclic ketones is demonstrated in a stereo-complementary fashion using the ketoreductases READH and Ch KRED20 for the production of ( S )- and ( R )-alcohols, respectively. The reaction accepts substrates with a five-, six- or seven-membered ring, and exhibits excellent stereoselectivity when using 2-propanol as both the ultimate reducing agent and cosolvent, achieve >99% ee in the majority of cases for both enantiomers.